Geometric thinking of Malaysian elementary school students - Md. Yunus, Aida Suraya; Mohd Ayub, Ahmad Fauzi; Tan, Tong Hock (International Journal of Instruction, 2019)
Geometry is one of the basic skills to be mastered in Malaysian mathematics education. However, there is not much information on geometry attainment of the elementary school students based on van Hiele's levels. The purpose of this study was to determine the van Hiele's levels of geometric thinking among the elementary school learners. Three different instructional strategies based on modules were tested on three groups of students ;(i) van Hiele's phases of learning (VH-PL) module that guides students through the van Hiele's learning process, (ii) van Hiele's theory which is integrated with the Google SketchUp software (VH-GSU) module and (iii) use of conventional instruction (NVH-CI) module which refers to teaching strategy without the use of van Hiele's theory of learning or any software in the teaching. This true experimental study involved 96 Year Five students of a Malaysian public school. Data were collected using Wu's Geometry Test (WGT) and sample responses identified by Fuys, Geddes, and Tischler (1988). Results showed that at the onset of the experiment, the students were operating at the lower levels of van Hiele's levels of geometric thinking. After the intervention, results of the WGT showed that most of the students in all three groups achieved a higher level of van Hiele's geometric thinking.